Tiller size/density compensation in grazed Tifton 85 bermudagrass swards - Sbrissia André Fischer; Silva Sila Carneiro da; Matthew Cory; Carvalho Carlos Augusto Brandão de; Carnevalli Roberta Aparecida; Pinto Luiz Felipe de Moura; Fagundes Jaílson Lara; Pedreira Carlos Guilherme Silveira (Pesquisa Agropecuária Brasileira, 2003)
The objective of this study was to evaluate the occurrence of the tiller size/density compensation mechanism in Tifton 85 bermudagrass swards grazed by sheep under continuous stocking. Treatments corresponded to four sward steady state conditions (5, 10, 15, and 20 cm of sward surface height), maintained by sheep grazing. The experimental design was a complete randomized block with four replicates. Pasture responses evaluated include: tiller population density, tiller mass, leaf mass and leaf area per tiller, and herbage mass. Tiller volume, leaf area index, tiller leaf/stem ratio, and tiller leaf area/volume ratio were calculated and simple regression analyses between tiller population density and tiller mass were performed. Measurements were made in December, 1998, and January, April, and July, 1999. The swards showed a tiller size/density compensation mechanism in which high tiller population densities were associated with small tillers and vice-versa, except in July, 1999. Regression analyses revealed that linear coefficients were steeper than the theoretical expectation of -3/2. Increments in herbage mass were attributable to increases in tiller mass in December and January. Leaf area/volume ratio values of Tifton 85 tillers were much lower than those commonly found for temperate grass species.